2014
DOI: 10.1002/embj.201387465
|View full text |Cite
|
Sign up to set email alerts
|

GTP hydrolysis by EF-G synchronizes tRNA movement on small and large ribosomal subunits

Abstract: Elongation factor G (EF-G) promotes the movement of two tRNAs and the mRNA through the ribosome in each cycle of peptide elongation. During translocation, the tRNAs transiently occupy intermediate positions on both small (30S) and large (50S) ribosomal subunits. How EF-G and GTP hydrolysis control these movements is still unclear. We used fluorescence labels that specifically monitor movements on either 30S or 50S subunits in combination with EF-G mutants and translocation-specific antibiotics to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
168
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(189 citation statements)
references
References 87 publications
20
168
1
Order By: Relevance
“…Consistent with recently published reports (47,48), we found that the H92A mutation introduced into wild-type EF-G decreased the GTPase activity of EF-G by at least 100-fold (Fig. S8A).…”
Section: Ef-g Adopts Different Conformations In Pre-and Posttranslocasupporting
confidence: 92%
“…Consistent with recently published reports (47,48), we found that the H92A mutation introduced into wild-type EF-G decreased the GTPase activity of EF-G by at least 100-fold (Fig. S8A).…”
Section: Ef-g Adopts Different Conformations In Pre-and Posttranslocasupporting
confidence: 92%
“…22. Our results suggest that EF-G serves as a force-generating motor via a power stroke in the early steps of translocation, supporting the proposal that energy released from GTP hydrolysis triggers EF-G conformational changes to promote translocation (24). The sequential motions of EF-G that follow the first stroke and complete…”
supporting
confidence: 79%
“…In this assay system, we measure the complete translocation cycle time from the association of EF-G·GTP to the pre-translocation ribosome to the release of EF-G·GDP from the post-translocation ribosome. This approach contrasts those based on fluorescence-labeled mRNA, fluorescence-labeled tRNAs or those with puromycin reactivity as a marker for the post-termination ribosomal complex (see Holtkamp et al [28]). The method has been used to determine how the Mg 2+ ion concentration affects the rate of translocation at high and low concentration of EF-G, how the rate of translocation varies with the distance between the translocated codon and the initiation codon and how SD-like sequences within ORFs affect the translocation rate.…”
Section: Introductionmentioning
confidence: 96%
“…[28], Cunha et al[33] and Savelsbergh et al[35], these approaches estimate but fractions of the total translocation time and the mechanistic interpretation of the results is sometimes difficult. For instance, Cunha et alused one and the same mRNA labeled with two different Effect of the free Mg 2+ concentration on the translocation rate in the long ORF.…”
mentioning
confidence: 98%